Government Efforts In Public Policy: Infographic And Distribution Of Covid 19 - Susanti, Selfi Ami; Othman, Lie; Prihatin, Panca Setyo; Teguh, Prio (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2020)
Abstract coronavirus 19 (Covid-19) is a global threat to millions of people. Major efforts in knowledge production have been made in recent months, requiring comprehensive analysis to examine research gaps and to help guide the agenda for further study. The method used is quantitative analysis. This study aims to determine the comparison of Covid 19 data in the West Nusa Tenggara region. The results showed that the publication of data by the Task Force and the Government of West Nusa Tenggara was different. The impact of this finding is that data availability has an effect on public opinion about data evaluation. Keywords : Covid 19, Government, and Policy.